2010
DOI: 10.1007/s10450-010-9257-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of N-hydrocinnamoyl-N-phenylhydroxylamine on pure minerals

Abstract: Equilibrium adsorption studies of N-hydrocinnamoyl-N -phenylhydroxylamine (HCNPHA) on galena, sphalerite, pyrite, chalcopyrite and quartz at pH 9 and 10 are reported. All adsorption isotherms followed Langmuir model, however, Freundlich type was observed for quartz. As HC-NPHA is a strong chelating agent, formation of monolayers by chemisorption appeared to be the most probable mechanism of adsorption on the base-metal sulphide minerals. Specific adsorption of HCNPHA on iron containing minerals, namely, chalco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Commonly, the two O atoms in carbonyl and hydroxyl groups of a hydroxamate molecule bond with metal cation to form a five-membered ring structure. The surface complexes of hydroxamic acid and metal species on mineral surface were also reported [8][9][10][11][12]. As a result, hydroxamic acids such as octyl hydroxamic acid (OHA), benzohydroxamic acid and salicylhydroxamic acid have been widely used as collectors for flotation recovery of metal oxide minerals including copper [13], tin [8], iron [14], tungsten [15], and rare earth minerals [9].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the two O atoms in carbonyl and hydroxyl groups of a hydroxamate molecule bond with metal cation to form a five-membered ring structure. The surface complexes of hydroxamic acid and metal species on mineral surface were also reported [8][9][10][11][12]. As a result, hydroxamic acids such as octyl hydroxamic acid (OHA), benzohydroxamic acid and salicylhydroxamic acid have been widely used as collectors for flotation recovery of metal oxide minerals including copper [13], tin [8], iron [14], tungsten [15], and rare earth minerals [9].…”
Section: Introductionmentioning
confidence: 99%
“…The shift energies of valence electrons on the surfaces of pyrrhotite (ET = 24 h) and serpentine, before and after treatment with OHA (OHA concentration: 5 × 10 −4 mol/L, pH = 8.0), are shown in Table 5, and the O1s and N1s spectra of pyrrhotite (ET = 24 h) and pyrrhotite (ET = 24 h) treated with OHA (OHA concentration: 5 × 10 −4 mol/L, pH = 8.0) are shown in Figures 7 and 8, respectively. The binding energy of O1s and Fe2p of pyrrhotite (ET = 24 h) underwent a change of 0.15 eV and 0.18 eV after OHA treatment, respectively, which indicated that the chemical environment of Fe and O atoms experienced changes, and OHA was chemically adsorbed on the surface of pyrrhotite (ET = 24 h) [25]. However, the binding energy of the O1s of serpentine had not changed in the presence of OHA.…”
Section: Xps Analysismentioning
confidence: 95%
“…Meanwhile, a new peak (398.88 eV) was observed after OHA treatment, as shown in Figure 8, which may correspond to an "O, N" four-ring chelate [30]. The binding energy of O1s and Fe2p of pyrrhotite (ET = 24 h) underwent a change of 0.15 eV and 0.18 eV after OHA treatment, respectively, which indicated that the chemical environment of Fe and O atoms experienced changes, and OHA was chemically adsorbed on the surface of pyrrhotite (ET = 24 h) [25]. However, the binding energy of the O1s of serpentine had not changed in the presence of OHA.…”
Section: Xps Analysismentioning
confidence: 99%
See 1 more Smart Citation